Characterization of some selected macroalgae extracts and assessment of their insecticidal and genotoxicity in Culex pipiens L. mosquito larvae - Dina A. Refaay; Mostafa M. El-Sheekh; Yasmin M. Heikal; Ahmed A. Rashed (Scientific Reports)
Abstract The continual use of synthetic insecticides to control mosquito larvae has severe implications for human health and the ecosystem, highlighting the need for alternative natural insecticides. Macroalgae may be a good alternative because of their biologically active metabolites with distinctive chemical structures that have been reported for their insecticidal properties. The study aimed to investigate the potential of different extracts from Jania rubens (Linnaeus) J.V.Lamouroux and Colpomenia sinuosa (Mertens ex Roth) Derbès & Solier as genotoxic and larvicidal agents against Culex pipiens Linnaeus larvae. The algae thallus was subjected to extraction using methanol, acetone, and methylene chloride. The phytochemical composition was quantified. The larvicidal activity of the different algae extracts was assessed against the third instar larvae of Culex pipiens. Genotoxic evaluation through comet assays and compound characterization by GC/MS was done. The results demonstrated that J. rubens methylene chloride extract exhibited the highest contents of phenolics, alkaloids, flavonoids, terpenoids, and tannins while C. sinuosa methanol extract demonstrated the highest levels of flavonoids, alkaloids, phenolics, and saponins. The larvicidal activity results revealed that J. rubens methylene chloride extract was the most toxic for C. pipiens larvae with LC50 = 9.30 ppm followed by C. sinuosa acetone extract with LC50 = 82.58 ppm after 72 h of exposure. At 50 and 250 ppm, J. rubens methylene chloride and C. sinuosa acetone extracts maintained 100 and 93.33% larval mortality rates, respectively. Comet assay results demonstrated the genotoxicity of both algae extracts in C. pipiens larvae. This study would be a beginning towards replacing chemical insecticides with algae-based bioinsecticides against C. pipiens mosquitos.